2017
DOI: 10.1002/cpt.656
|View full text |Cite
|
Sign up to set email alerts
|

Association of Time‐Varying Clearance of Nivolumab With Disease Dynamics and Its Implications on Exposure Response Analysis

Abstract: Nivolumab is a human monoclonal antibody that blocks the interaction between PD-1 programmed death-1 (PD-1) and its ligands, PD-L1 and PD-L2. Nivolumab demonstrated efficacy in clinical trials for various types of cancer. A time-varying clearance was identified for nivolumab. We show that the change of clearance over time is associated with the post-treatment effects: clearance decreases when disease status improves. This interaction between posttreatment effects and drug exposure may lead to a biased steep es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
264
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(294 citation statements)
references
References 11 publications
18
264
0
1
Order By: Relevance
“…This idea is consistent with our observations and a report by Liu et al 5. on clearance of nivolumab.…”
supporting
confidence: 95%
“…This idea is consistent with our observations and a report by Liu et al 5. on clearance of nivolumab.…”
supporting
confidence: 95%
“…This finding from population PK analysis is consistent with noncompartment analysis, where subjects with solid tumors had approximately 2‐fold higher clearance as compared with subjects with GBM. Disease status has been reported to have a significant impact on the clearance of monoclonal antibodies in the literature . Body weight was identified as a significant covariate on depatux‐m clearance.…”
Section: Discussionmentioning
confidence: 95%
“…[30][31][32]44,70 Although these changes in clearance were not considered clinically relevant (as per comments in each package insert), recent PK modeling analyses-in several cases prompted by the regulatory authorities-taking into account the time-varying nature of this parameter have shown that clearance changes appear to be associated with response to treatment. 51,56,74,75 Patients who benefited from treatment with nivolumab, pembrolizumab, or atezolizumab with respect to tumor response and improved OS had lower clearance; tumor shrinkage in patients treated with durvalumab was also associated with decreased clearance. One explanation for this observation is that, as disease state improves, a reduction in cachexia would result in lowered catabolism and thus reduced antibody clearance.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…One explanation for this observation is that, as disease state improves, a reduction in cachexia would result in lowered catabolism and thus reduced antibody clearance. 74,75 The mAbs commonly display modest interpatient variability in PK, and population PK is used to identify intrinsic and extrinsic covariates that can explain part of the observed variability. 60 The covariates chosen for investigation focused primarily on intrinsic factors such as sex and age, as well as those relating to disease state (for example, tumor type, tumor burden, and baseline parameters such as performance status, lactate dehydrogenase [LDH], and albumin), which might rationally be expected to differ between patients and so contribute to interpatient PK variability.…”
Section: Pharmacokineticsmentioning
confidence: 99%